A Study on Dual-Generalized Complex and Hyperbolic-Generalized Complex Numbers - Gurses, Nurten; Senturk, Gulsum Yeliz; Yuce, Salim (GAZI UNIV, 2021)
This work is intended to introduce the theories of dual-generalized complex and hyperbolic-generalized complex numbers. The algebraic properties of these numbers are taken into consideration. Besides, dual-generalized complex and hyperbolic-generalized complex valued functions are defined and different matrix representations of these numbers are examined. Moreover, a remarkable classification are given for special cases and the set of complex-generalized complex numbers are mentioned.
Keywords: Generalized complex numbers; Dual-generalized; Complex nnumber; Hyperbolic-generalized; Complex number; Science & Technology - Other Topics